Hierarchical Carbon Nanofibers@Nickel Phosphide Nanoparticles for High‐Performance Supercapacitors. Issue 2 (3rd December 2021) - Xu, Jing; Schulte, Anna; Schönherr, Holger; Jiang, Xin; Yang, Nianjun
Abstract : The design and synthesis of novel active materials as the capacitor electrodes is of great significance to fabricate high‐performance supercapacitors, namely those with large and stable capacitances as well as high power and energy densities. Herein, binder‐free and hierarchical carbon nanofibers@nickel phosphide nanoparticles are grown in a chemical vapor deposition reactor, where Ni5 TiO7 nanowires and a TiO2 outer layer are in situ converted into interconnected nickel phosphide nanoparticles and a TiC layer, respectively. The initially formed hierarchical nickel phosphide nanoparticles boost the catalytic growth of CNFs, leading to the generation of a 3D interconnected texture, which features a high specific surface area and excellent conductivity. The combination of this nanocomposite as a capacitor electrode with redox electrolyte of 0.05 m Fe(CN)6 3−/4− generates a specific capacitance of 59.3 mF cm −2 at a current density of 5 mA cm −2 . This capacitor electrode exhibits 95% of its initial capacitance even after 10 000 charging/discharging cycles. The as‐fabricated supercapacitor device offers an energy density of as high as 27.4 Wh kg −1 accompanied with a power density of 7.25 kW kg −1 . The proposed method thus provides an approach to produce binder‐/current‐collector‐free capacitor electrodes, which can be utilized to fabricate high‐performance supercapacitors. Abstract : An in situ grown carbon nanofiber on a Ti substrate is free of binders and current collectors. Stemming from its 3D and interconnected texture, it features a high specific surface area and an excellent conductivity. Its integration as a capacitor electrode with redox electrolytes produces supercapacitors with big and stable capacitances as well as high power and energy densities.